Case report: successful long-term management of a low-birth weight preterm infant with compound heterozygous protein C deficiency with subcutaneous protein C concentrate up to adolescence - Pöschl, Johannes; Behnisch, Wolfgang; Beedgen, Bernd; Kuß, Navina (Frontiers in Pediatrics, 2021)
Homozygous/compound heterozygous forms of congenital protein C deficiency are often associated with severe antenatal and postnatal thrombotic or hemorrhagic complications. Protein C deficiency frequently leads to severe adverse outcomes like blindness and neurodevelopmental delay in children and may even lead to death. The most widely used long-term postnatal treatment consists of oral anticoagulation with vitamin K antagonists (e.g., warfarin), which is supplemented with protein C concentrate in acute phases. Subcutaneous infusions have been described in infants mostly from 2 months of age after severe postnatal thrombosis, but not in newborns or premature infants without thromboembolism. We report the first case of a compound heterozygous protein C-deficient preterm infant, born at 31+5 weeks of gestation to parents with heterozygous protein C deficiency (protein C activity 0.9% at birth). We focus on both prenatal and perinatal management including antithrombotic treatment during pregnancy, the cesarean section, and continuous postnatal intravenous and consecutive subcutaneous therapy with protein C concentrate followed by a change of therapy to direct oral anticoagulants (DOACs) (apixaban). We report successful home treatment with subcutaneous protein C concentrate substitution overnight (target protein C activity >25%) without complication up to 12.5 years of age. We propose that early planned cesarean section at 32 or preferably 34 weeks of gestation limits potential maternal side effects of anticoagulation with vitamin K antagonists and reduces fetal thromboembolic complications during late pregnancy. Intravenously administered protein C and early switch to subcutaneous infusions (reaching about 3 kg body weight) resulted in sufficient protein C activity and has guaranteed an excellent quality of life without any history of thrombosis for 13 years now. In older children with protein C deficiency, as in our case, DOACs could be a new therapeutic option.
Gesehen am 21.10.2021